Effectiveness of teaching evidence-based medicine to undergraduate medical students: A BEME systematic review - Ahmadi, Seyed-Foad; Baradaran, Hamid R; Ahmadi, Emad (Medical teacher, 2015)
Abstract Background: Despite the widespread teaching of evidence-based medicine (EBM) to medical students, the relevant literature has not been synthesized appropriately as to its value and effectiveness. Aim: To systematically review the literature regarding the impact of teaching EBM to medical students on their EBM knowledge, attitudes, skills and behaviors. Methods: MEDLINE, SCOPUS, Web of science, ERIC, CINAHL and Current Controlled Trials up to May 2011 were searched; backward and forward reference checking of included and relevant studies was also carried out. Two investigators independently extracted data and assessed the quality of the studies. Results: 10,111 potential studies were initially found, of which 27 were included in the review. Six studies examined the effect of clinically integrated methods, of which five had a low quality and the other one used no validated assessment tool. Twelve studies evaluated the effects of seminars, workshops and short courses, of which 11 had a low quality and the other one lacked a validated assessment tool. Six studies examined e-learning, of which five having a high or acceptable quality reported e-learning to be as effective as traditional teaching in improving knowledge, attitudes and skills. One robust study found problem-based learning less effective compared to usual teaching. Two studies with high or moderate quality linked multicomponent interventions to improved knowledge and attitudes. No included study assessed the long-term effects of the teaching of EBM. Conclusions: Our findings indicated that some EBM teaching strategies have the potential to improve knowledge, attitudes and skills in undergraduate medical students, but the evidenced base does not demonstrate superiority of one method. There is no evidence demonstrating transfer to clinical practice.